The Infrastructural Function: A Relational Theory of Infrastructure for Writing Studies. (July 2019) - Read, Sarah
This article theorizes the term infrastructure as a framework for articulating how writing products, activities, and processes underwrite organizational life in technical organizations. While this term has appeared broadly in writing studies scholarship, it has not been systematically theorized there as it has been in other fields such as economics, computing, and information science. This article argues for a four-part framework that incorporates and builds on Star and Ruhleder's relational theory of infrastructure. Fieldwork from a federally funded supercomputing center for scientific research operationalizes the theory for its contributions to writing studies scholarship and its applications for industry and writing pedagogy.